Implementation of a Room Temperature Control System in Patient Rooms with Positive COVID-19 Patients - Khaeriyah Adri; Jamaluddin Ahmad; Zulkarnain Sulaiman; Pratiwi Ramlan; Mardhatillah; Madaling (Indian Journal of Forensic Medicine & Toxicology, 2021)
Technology development triggers the development of human thought to be able to create innovations toimprove performance. The increasing cases of COVID-19 infection mean that you should seek to breakthe chain of this virus by self-isolation. However, the purpose of self-isolation rooms should be consideredespecially at rooms without air conditioning. These technological innovations are needed to provide comfortfor patients and families. The goal of this study is to give families of COVID-19 positive patients easyaccess to their loved ones’ rooms without having to physically enter the room. The procedure is artificialintelligence with Arduino programming using Arduino IDE that is part of the micro controller board. Microcontrolledsystems can be thought of as being like an integrated computer system packaged in a single chip.The result showed the temperature control system tool was able to work well with a temperature error rateof 1.13%. It is known that in COVID-19-positive patients it is very helpful for families to monitor roomtemperature and for patients to rest comfortably.